Ribboncraft - Beverley, Deena (Mitchell Beazley, 1997)
This book Presents more than twenty Victorian-style projects that can be made with ribbons, explaining the types of ribbons and their characteristics, as well as embroidery stitching.
Keywords: Hand Weaving; Ribbon Flowers; Ribbon Work; Ribbons